Anode optimization based on gradient porous control medium for passive liquid-feed direct methanol fuel cells. (April 2016) - Yuan, Wei; Yan, Zhiguo; Tan, Zhenhao; Wang, Aoyu; Li, Zongtao; Tang, Yong
Abstract: The direct methanol fuel cell (DMFC) is a potential candidate to be used as a portable power source which still faces great challenges in structure optimization because of complex interactions and even conflicts between the reactant and product managements. This work presents an effective method for the anode optimization by using a gradient porous medium to realize more active control of the anode mass transfer mechanisms of a passive liquid-feed DMFC. This functional medium is made of a self-developed metal fiber sintered felt based on multi-tooth cutting and high-temperature sintering. Its structural features and processing parameters can be adaptively controlled according to the application requirement. Results indicate that the porosity, assembly pattern and thickness of this gradient porous medium have great effects on the cell performance. The DMFC is insensitive to the change of sintering process. The use of a gradient porosity promotes a higher cell performance than the uniform structure, especially when a lower porosity is used inward. How the methanol concentration affects the cell performance is also discussed in this study. Highlights: A gradient porous medium is used for mass transfer control in a passive DMFC. The gradient porous medium is made of multi-layers of copper fiber sintered felt. Results confirm the advantage of using a gradient porosity for anode optimization. The structure of the porous control medium has great effect on the fuel cell.